SEPSIS-INDUCED ACUTE KIDNEY INJURY: BIOMARKERS FOR DIAGNOSIS - Marcelino-Rodrigues, Vanessa; Caroline Silva Freitas, Ana; Jose Figueiredo, Maria; Reis Machado, Juliana; Borges de Menezes, Liliana; Figueiredo Soave, Danilo; Rubia Nunes Celes, Mara (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Sepsis is a major global health problem leading to the increased incidence of death in intensive care units. In recent years, despite technological advances, the number of cases has grown significantly. Among the main complications presented by septic patients, acute renal dysfunction is largely responsible for the high mortality rate. Initially, the reduction of renal function is associated with focal tubular injury with preserved glomerular morphology and systemic hemodynamic alterations. During sepsis development, the progressive decrease in urinary volume and reduction of the glomerular filtration rate associated with increased serum levels of urea and creatinine are considered classic markers of severe kidney injury. Despite the valuable role of these serum markers regarding renal function, these data provide an incomplete scenario of the patient, since many renal disorders may occur in individuals with increased plasma concentrations of urea and creatinine. Taking into account the important role of systemic inflammatory processes in the development of acute kidney injury induced by sepsis, the search for new markers presenting high sensitivity and specificity capable of detecting early renal injury is still necessary. Thus, the present review summarizes important aspects of pathophysiology of acute kidney dysfunction induced by sepsis and presents an updated view of possible new biomarkers associated with the development of acute kidney injury. Understanding these markers allows important advances leading to new therapeutic approaches, indicating a new horizon in the diagnosis and treatment of acute kidney injury in sepsis.